Maternal Age at Marriage and the Incidence of Stunting Among Children Under Five: A Cross-Sectional Study in Sleman Regency, Indonesia - Dewi Rokhanawati; Nidatul Khofiyah; Rhipiduri Rivanica; Kriska Afri Juliandari; Yuriska Verina (Media Kesehatan Politeknik Kesehatan Makassar, 2026)
Stunting continues to be a significant public health concern in Indonesia and is strongly associated with maternal and reproductive determinants. One recognized factor contributing to stunting is early marriage, which may increase biological, psychosocial, and socioeconomic vulnerability among mothers. This study aimed to examine the relationship between maternal age at marriage and stunting among children under five in Sleman Regency, Indonesia, while accounting for selected maternal and child characteristics. A cross-sectional design was conducted from October to December 2025 across three primary health centers in Sleman, involving 60 mother–child pairs selected through total sampling. Stunting was defined as a height-for-age z-score below −2 standard deviations based on WHO criteria. Independent variables included maternal age at marriage, maternal sociodemographic characteristics, birth spacing, exclusive breastfeeding history, child sex, and health center coverage area. Data were analyzed using univariate, bivariate, and multivariate methods with Firth’s logistic regression. Adjusted odds ratios with 95% confidence intervals were calculated, and model selection was guided by the Akaike Information Criterion. Stunting prevalence was 16.7%. Early maternal marriage, female sex, and inadequate birth spacing were significantly associated with higher stunting risk. These findings underscore the importance of delaying marriage and strengthening reproductive health interventions.